2018
DOI: 10.1038/s41598-018-23372-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a dimeric-cRGD peptide for targeted PET-CT imaging of peripheral angiogenesis in diabetic mice

Abstract: The αV β3 integrin plays an important role in many physiological functions and pathological disorders. αV β3 is minimally expressed in normal quiescent endothelial cells, but significantly upregulated during neovascularization. In this study, we evaluated a 64Cu-labeled dimeric cRGD tracer targeted at αV β3 integrin and report its applicability to assess peripheral angiogenesis in diabetes mellitus (DM). We established a murine model of type-1 DM characterized by elevated glucose, glycated serum protein (GSP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…All experiments were performed according to the guiding principles of the American Physiologic Society and approved by the Institutional Animal Care and Use Committee at the University of Illinois at Urbana-Champaign. Hindlimb ischemia was induced in 2-3-month-old male C57BL/6 mice (Jackson Laboratories, USA) using an already established protocol 48 . The mice were anesthetized with 1-3% isoflurane for surgical intervention and imaging.…”
Section: Methodsmentioning
confidence: 99%
“…All experiments were performed according to the guiding principles of the American Physiologic Society and approved by the Institutional Animal Care and Use Committee at the University of Illinois at Urbana-Champaign. Hindlimb ischemia was induced in 2-3-month-old male C57BL/6 mice (Jackson Laboratories, USA) using an already established protocol 48 . The mice were anesthetized with 1-3% isoflurane for surgical intervention and imaging.…”
Section: Methodsmentioning
confidence: 99%
“…αVβ3 integrin is minimally expressed in normal quiescent endothelial cells but significantly upregulated during neovascularization. A previous study showed CD31-positive endothelial cells within the capillaries and small arterioles of non-diabetic ischemic hindlimb sections, which correlated with high αVβ3 expression ( Hedhli et al, 2018 ). However, this finding has not been tested in a hindlimb ischemic disease model.…”
Section: Introductionmentioning
confidence: 84%
“…Similar to solid tumors, αVβ3 integrin is highly expressed in nondiabetic ischemic murine hindlimb ( Hedhli et al, 2018 ). Our findings are consistent with previous reports indicating that a low dose of cilengitide promotes angiogenesis in tumor models ( Reynolds et al, 2009 ; Wong et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of [ 18 18]-Galacto-RGD within the infarcted area peaked seven days post MI, correlated strongly with newly formed vessels and it could be blocked by a competitive inhibitor, which suggests the successful imaging of angiogenesis in the process of myocardial healing [ 27 ]. Various independent research groups were able to validate the concept of α v β 3 -integrin imaging—with both SPECT and PET tracers—as a surrogate marker for angiogenesis in the healing process of ischemically damaged myocardium [ 13 , 28 , 29 ] and skeletal muscle [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%